Hedge Fund Voluntary Disclosure - Cassar, Gavin J.; Gerakos, Joseph J.; Green, Jeremiah R.; Hand, John R. M.; Neal, Matthew (The Accounting Review, 2018)
ABSTRACT Using a dataset of 3,234 letters sent by 434 hedge funds to their investors during 1995–2011, we study what motivates hedge fund managers to make voluntary disclosures. Contrary to the hedge fund industry's reputation for opacity, we observe that managers provide their investors with an array of quantitative and qualitative information about fund returns, risk exposures, holdings, benchmarks, performance attribution, and future prospects. We find that the tensions between the agency costs faced by investors and the proprietary costs faced by managers affect fund disclosures. Consistent with managers reducing proprietary costs, better-performing funds disclose less quantitative data about performance and holdings, and consistent with the presence of agency costs, riskier funds disclose less quantitative information about performance and assets under management.